A vibroacoustic model of a reduction line of a gas installation - ENGEL, Zbigniew; PANUSZKA, Ryszard; MENŻYŃSKI, Mieczysław (Archives of Acoustics, 1984)
This paper proposes a method for predicting the sound power level of a reduction line of a gas installation, based on a vibroacoustic cylindrical equivalent model. This model was verified experimentally on a real object. It permits approximate prediction of the sound power level of a reduction line, depending on its technological and structural parameters, particularly for medium and high frequencies.